Development of a Web-Based Teacher Attendance System in Government Agencies: A Case Study at the Ministry of Religious Affairs - Assyifaurrohmah, Farwah; Mubin, Ahmad Fuzul; Tabrani, Ahmad Tabrani (Universitas Amikom Yogyakarta, 2025)
Objective: This study addresses the issues of inefficiency and lack of transparency in manual attendance recording systems in government institutions, particularly in the Ministry of Religious Affairs. The study aims to develop a web-based teacher attendance information system that addresses the inaccuracy and susceptibility to manipulation found in conventional paper-based methods, while improving administrative accountability.Method: The system was developed using an iterative software engineering approach that integrates comprehensive needs analysis, modular design architecture, and functional testing stages. The methodology combines web-based technology with user-centered interface design, accommodating the needs of administrative staff and teaching staff. The development phase includes gathering stakeholder requirements, planning the system architecture, implementation using the Django framework, and systematic validation procedures.Results: The implemented system successfully demonstrated improved accuracy in attendance recording, automatic validation of working hours, comprehensive absence history tracking, and Excel data export capabilities. Initial testing revealed increased reporting efficiency and a significant reduction in administrative processing time. The system achieved seamless integration with existing government workflows while maintaining data integrity and security standards.Contribution: This research contributes innovative solutions specifically tailored to Indonesian government institutions, bridging the integration of information technology with human resource management governance. The study presents a strategic digital transformation approach for public sector administrative services, offering a replicable model for similar government organizations seeking to modernize their attendance management systems.